Industrial Revolution: A History of Industrial Revolution and Its Influence in Manufacturing Companies - Nurdiana nurdiana; Moses Glorino Rumambo Pandin (Historia Madania: Jurnal Ilmu Sejarah, 2021)
Before the existence of industrial technology, people in doing their job using their power. People were able to produce goods and sell services with their power. These activities are ineffective because they are constrained and take a long time, so the discovery of industrial technology is today. This study aims to determine the meaning of the industrial revolution, the history and development of the industrial revolution 1.0 to 4.0, the relationship between the industrial revolution and Indonesian history, and the influence of the industrial revolution in Indonesian manufacturing. Indonesian people do not understand what revolution means and how it relates to Indonesian history, where the current and former situation is very different because of a revolution, especially the industrial revolution. The discovery of industrial technology or industrial revolution makes human development become advanced and rapidly growing. In this study, the author uses a method in the form of a Literature Review (LR) or a literature review and data obtained from several articles that have been published and registered online. Technology is believed by many people to make their work easier and takes a short time. The development of technology became necessary because of the emergence of the industrial revolution 4.0 that changed human life. This article tries to review the understanding of the industrial revolution, its development history, and its influence on Indonesian manufacturing companies. The limitation or weakness of this research lies in the research process, namely the author's weakness in collecting the reference sources used.